ESTETIKA KULINER MEMPENGARUHI CITRA DESTINASI, KEPUASAN WISATAWAN, DAN LOYALITAS WISATAWAN DI KOTA TERNATE - Fardin Darmin; Ida Hidayanti; Johan Fahri (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
The purpose of this research is to examine the relationship between culinary aesthetics, destination image, tourist satisfaction, and tourist loyalty in Ternate City. This type of research is an explanatory research with a quantitative approach. There are four variables used, namely culinary aesthetic variables, destination image, tourist satisfaction variable, and tourist loyalty variable. Data collection was obtained through distributing questionnaires to 120 respondents. The sampling technique used purposive sampling with a population of domestic tourists from Ternate City who visited at least two times to culinary tourism in Ternate City. The data analysis of this research used descriptive analysis and path analysis. The results of the study prove that the culinary aesthetic variable has a significant effect on the image of the destination, the image of the destination has a significant effect on the tourist loyalty variable. This study also found an indirect effect of port aesthetics on tourist loyalty through destination image and tourist satisfaction. Based on the results of the study, it is recommended that the Regional Government and tourism business actors maintain the image of local culinary in Ternate City and increase the intensity of tourist visits by promoting all types of tourist attractions including local culinary and optimizing tourist attractions in the diverse Ternate City through the image of the destination.